INTEGRATING VOCATIONAL STREAM IN SECONDARY SCHOOL: A QUALITATIVE CASE STUDY - Mohd. Hashim, Mohamad Hisyam; Ibrahim, Abdullah (Journal of Technical Education and Training, 2010)
Vocational stream is a new set-up in the education system of developing countries especially for countries with low population and limited area of land. Nevertheless, this countries are working on providing vocational education to their citizen particularly for their youngsters in secondary school. There are few important elements or items that can be used as guidence in a certain implementation that might be the basics of the implementation. The qualitative methodology (Inteviews, Documents analysis and observation) are used. Research findings show that there are some items that can be adopted as the Guidelines On International Best Practices In Integrating Vocational Education In Secondary School especially for the vocational streamed school. It is also found that, it is still too soon for the implementation of vocational stream in the existing secondary schools if the basic requirements for it are not being formed or improved. It is suggested that, the implementation of International Best Practices in Integrating TVET in the Secondary School which was also being suggested previously for other developing countries by model pathway of voational stream student.